2021
DOI: 10.3390/nu13103477
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nutritional Status on Polypharmacy, Cognition, and Functional Capacity of Institutionalized Elderly: A Systematic Review

Abstract: Adequate nutritional status is necessary for the proper management of polypharmacy, the prevention of cognitive decline, and the maintenance of functional capacity in activities of daily living. Although several studies validate this fact for the general elderly population, data on institutionalized seniors concerning this relation are scarce. A systematic review was performed according to the PRISMA guidelines, aiming to study the potential correlation between nutritional status and polypharmacy, cognitive de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…It has been reported that the provision of good nutrition in senior citizen homes leads to better cognitive functioning as well as physical and mental health [17]- [20]. It has also been found that greater wellbeing 1176 (2023) 012016 IOP Publishing doi:10.1088/1755-1315/1176/1/012016 3 is based on greater food satisfaction including e.g.…”
Section: Significance/situation Of Food Services For Residents In Sen...mentioning
confidence: 99%
“…It has been reported that the provision of good nutrition in senior citizen homes leads to better cognitive functioning as well as physical and mental health [17]- [20]. It has also been found that greater wellbeing 1176 (2023) 012016 IOP Publishing doi:10.1088/1755-1315/1176/1/012016 3 is based on greater food satisfaction including e.g.…”
Section: Significance/situation Of Food Services For Residents In Sen...mentioning
confidence: 99%
“…[14,15] Studies have shown that the prevalence of in-adequate nutrition among the elderly ranges from 2% to 8% in the literature and from 20% to 60% in clinical settings. [14,[16][17][18] The decrease in biopsychosocial functional capacity and loss of abilities in the elderly result in a higher incidence of chronic health problems (hypertension, diabetes mellitus, coronary artery disease, chronic obstructive pulmonary disease, stroke, depression), increased dependency on social and psychological support, and the need for the assistance of others. [19,20] Physiological and psychosocial changes in old age, along with resulting issues, impact individuals' quality of life, [21] increase the risk of illness and death, and impose a significant societal cost from a social and economic perspective.…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] Studies have shown that the prevalence of in-adequate nutrition among the elderly ranges from 2% to 8% in the literature and from 20% to 60% in clinical settings. [14,16–18]…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] The risk of malnutrition is an important predictor of functional capacity in the elderly population. 16,17 In summary, medications with anticholinergic properties are consistently associated with worse outcomes such as impaired physical function, falls, malnutrition risk, and cognitive impairment in older adults. 13,14,[18][19][20] Despite increasing evidence of unexpected medical problems, the number of medications with high anticholinergic activity prescribed to older adults has increased.…”
mentioning
confidence: 99%
“…Also, polypharmacy and anticholinergic drug burden had a significant link with malnutrition 13–15 . The risk of malnutrition is an important predictor of functional capacity in the elderly population 16,17 . In summary, medications with anticholinergic properties are consistently associated with worse outcomes such as impaired physical function, falls, malnutrition risk, and cognitive impairment in older adults 13,14,18–20 .…”
mentioning
confidence: 99%